Learning Experiences and Student Independence in AI-Based Hijaiyah Letter Pronunciation Practice in Elementary Schools - Ariyanto, Davi; Gulo, Rizka Jadidah Gulo; Putri, Helena; Aziz, Alif Ikhwan (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze learning experiences and student independence in AI-based Hijaiyah letter pronunciation practice in elementary schools. The use of Artificial Intelligence (AI) in learning provides opportunities to create more interactive, adaptive, and personalized learning processes based on students’ needs. This research employed a qualitative approach with a descriptive method. The participants were elementary school students engaged in Hijaiyah pronunciation learning using AI-based applications. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the use of AI in Hijaiyah pronunciation practice enhances students’ learning experiences, making them more engaging and enjoyable. In addition, students demonstrated increased learning independence, as indicated by their ability to practice independently, repeat materials as needed, and receive immediate feedback from the system. This study concludes that AI-based learning is effective in improving both learning experiences and student independence in Hijaiyah letter learning at the elementary school level.